Topological tailoring-induced Dirac cone in ultrathin niobium diboride nanosheets for electrocatalytic sulfur reduction reaction. (March 2023) - Zhao, Yuwei; Zhang, Linghai; Xiang, Jianglu; Chen, Xinyu; Zhu, Chao; Wang, Kaixi; Li, Junfeng; Ma, Huifang; Song, Xuefen; Wang, Lin; Zha, Chenyang
Abstract: Two-dimensional topological Dirac materials with novel electronic structures have attracted increasing attention in materials science, where the Weyl fermions can emerge in topological insulating multilayers with unusual quantum transport properties. However, their practical catalytic performance is seldom reported. Here, we design ultrathin niobium diboride (NbB2 ) nanosheets by utilizing topological electronic states to power catalytic activity. In the lithium-sulfur batteries, the stable topological surface states of NbB2 with high carrier mobility are a recipe for high-activity catalysts to spur the sluggish electrocatalytic sulfur reduction reaction, which originates from the Dirac cone electronic structure. Most remarkably, it delivers stable capacities with 1500 cycles under the 3.6 mA/cm 2 (3 C), which is far superior to most electrode catalysts. The proposed functional Weyl and/or Dirac materials would have broad applications in other related fields such as the hydrogen evolution reaction, nitrogen reduction reaction, and energy conversion. Graphical abstract: Image 1 Highlights: Two-dimensional niobium diboride nanosheets with Dirac cone. The high carrier mobilities originating from the linear bands of a Dirac cone. The sluggish electrochemical reaction of polysulfide is accelerated by the niobium diboride. Excellent long-term cycling performance at 3 C after 1500 cycles.